Age-Related Shifts in Bacterial Diversity in a Reef Coral. - Alex D Williams; Barbara E Brown; Lalita Putchim; Michael J Sweet (PLoS ONE, 2015)
This study investigated the relationship between microbial communities in differently sized colonies of the massive coral Coelastrea aspera at Phuket, Thailand where colony size could be used as a proxy for age. Results indicated significant differences between the bacterial diversity (ANOSIM, R = 0.76, p = 0.001) of differently sized colonies from the same intertidal reef habitat. Juvenile and small colonies (< 6 cm mean diam) harboured a lower bacterial richness than medium (~ 10 cm mean diam) and large colonies (> 28 cm mean diam). Bacterial diversity increased in a step-wise pattern from juveniles < small < medium colonies, which was then followed by a slight decrease in the two largest size classes. These changes appear to resemble a successional process which occurs over time, similar to that observed in the ageing human gut. Furthermore, the dominant bacterial ribotypes present in the tissues of medium and large sized colonies of C. aspera, (such as Halomicronema, an Oscillospira and an unidentified cyanobacterium) were also the dominant ribotypes found within the endolithic algal band of the coral skeleton; a result providing some support for the hypothesis that the endolithic algae of corals may directly influence the bacterial community present in coral tissues.